Population Dynamics and Tree Damage of the Invasive Chestnut Gall Wasp, Dryocosmus kuriphilus, in Its Southernmost European Distributional Range - Javier Quinto; María Eva Wong; Juan Ramón Boyero; José Miguel Vela; Martin Aguirrebengoa (Insects, 2021)
The invasive chestnut gall wasp (CGW), Dryocosmus kuriphilus, the worst pest of chestnut cultivation, has spread worryingly throughout Europe in less than 20 years. Despite the great concern around this pest, little is known about the status in its southernmost distribution in continental Europe. We assessed spatio-temporal patterns in the population dynamics, phenology and tree damage caused by CGW in southern Spain. Likewise, the relationship between these variables and thermal trends was evaluated. We found strong variation in the population dynamics and flight phenology among localities and over time, which were highly influenced by changes in thermal regimes. Specifically, warmer localities and vegetative periods promoted higher population densities, a partial increase in the survival of immature stages, and advanced flight activity. Moreover, tree damage evolved differently over time in each locality, which suggests that local conditions may determine differences in damage evolution. Our findings evidence that great spatio-temporal variability in the CGW populations takes place across invaded areas in its southernmost European distributional range. Although control mechanisms have been introduced, implementation of further control and management measures are critical to cope with this main threat for the chestnut industry and to prevent its spread to nearing chestnut-producing areas.